Suscetibilidade dos recifes de Abrolhos aos eventos de branqueamento de corais - Samira da Conceição Sabadini (2017)
Marine ecosystems are fundamental to the maintenance of life on Earth. Among them, the coral reefs that are considered highly productive, diverse and complex stand out. However, these ecosystems suffer many threats, including coral bleaching. Bleaching occurs mainly in response to positive sea surface temperature anomalies. The objective of this work was to model the susceptibility of Abrolhos reefs (southern Bahia) to bleaching and, more specifically, to generate a map of susceptibility to bleaching of Abrolhos reefs during the summers of 2001, 2002, 2003, 2005 and 2016. Our results show that in 2001, 20% of the reef area presented low susceptibility to bleaching, while 80% presented medium susceptibility. 2002 was the year with the lowest susceptibility, being very low in 18% of the area and low in 82%. In 2003, 75% of the area showed low susceptibility and 25% medium. In 2005, the area of medium susceptibility reached 90%, while 10% presented low susceptibility. In 2016, 19% of the area presented medium and 81% high susceptibility. The year 2016 showed the highest susceptibility between the years studied, suggesting a higher percentage of bleached colonies, which is corroborated by the fact that this year was considered by NASA and NOAA as the warmest year since 1880. The results also show that the bleaching pattern is spatially differentiated. The reefs from the coastal arch of Abrolhos present the greater susceptibility to bleaching. Exception is made to Timbebas reefs that, although located in the coastal arch, are more similar to the outer arch reefs that are less susceptible to the bleaching.